Keseimbangan Antara Penyerahan Kewenangan dan Penyerahan Sumber Penerimaan Daerah di Indonesia - Khairi, Halilul (Jurnal Bina Praja, 2021)
Since 1946, Indonesia has adopted a decentralization policy that impacts the transfer of authority to regulate and administer government affairs in the regions, followed by financing to manage these affairs. In a unitary state, the power source, both in terms of financial management and administrative power, rests with the central government. This study uses a descriptive qualitative method to explain the history of the development of authority and financial balance policies in Indonesia and the meaning of decentralization policies in Indonesia. Quantitative descriptive was used to analyze data regarding the implementation of regional government affairs, personnel expenditure ratios, comparison of central and regional expenditures, and other data related to burdens and revenues between the center and the regions. This study found that the central government has recognized regional independence through income sources managed by themselves and reduced transfer funds that aim to cover the lack of regional revenues. The provision of sources of revenue from the central government to the regions is not proportional to the ratio of the burden given. The results of this study indicate that the load is inversely related to the budgetary capacity between the government and local governments. The imbalance between the workload and the source of revenue received by the region is the low ability of the region to provide basic services that are the authority.